Using Education Technology to Support Students with Special Educational Needs and Disabilities in Low- and Middle-Income Countries - Coflan, Caitlin Moss; Kaye, Thomas (EdTech Hub, 2020)
This brief focuses on how policymakers can make decisions about EdTech to support learners with special educational needs and/or disabilities (SEND) while offering policymakers the rationale and tools to move towards an inclusive approach. It also includes a detailed annex with descriptions, costs, availability, and examples of accessible and assistive technologies.
Keywords: F: Helpdesk response; L:Special education needs and disabilities (SEND); LP: English; _DOILIVE; _EdTechHub_Output; _GS:indexed; _MELA_seen; ___working_potential_duplicate; _cover:v1; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoETH; dode_eth-src-dode

EdTech for Climate Resilience: A Rapid Evidence Review - Brugha, Meaghan; Azfal, Nimra; Emerusenge, Aime Parfait; Zazai, Rozina; Nagol, Elias (EdTech Hub, 2025)
This Rapid Evidence Review provides a synthesis of evidence related to the use of educational technology for building climate resilience within education systems in low- and middle-income countries. The primary objective of the review is to provide educational stakeholders with an overview of how technology could be effectively leveraged in these contexts, highlighting key design considerations for and potential barriers to effective implementation. The review looked at evidence generated between 2014 and 2025 on how EdTech has or could be used to build climate resilient education systems. An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

Pakistan Digital Learning Landscape Analysis - Zubairi, Asma; Khalayleh, Abdullah; Baloch, Imdad; Mazari, Haani; Kaye, Tom; Groeneveld, Caspar (EdTech Hub, 2022)
The Covid-19 pandemic has resulted in a dramatic increase in the role educational technology (EdTech) plays in education delivery. As schools have closed worldwide, EdTech has played a critical role in keeping children learning. However, as the pandemic has persisted, the optimism around EdTech has plateaued. It has given way to fears that children who are using EdTech are not learning, and that the most marginalised children are falling further behind due to the emergence of a digital divide. On average, only 34% of households across Pakistan have digital access and only 14% have access to laptops or computers. The access challenge is further intensified by demographics including gender, locality, and socio-economic status. This divide must be addressed if EdTech is to support effective learning for all children across all contexts in Pakistan. If left unaddressed, EdTech interventions can exacerbate a digital divide that further compounds the disadvantage of marginalised groups. Across the world, UNICEF has supported governments globally to deploy EdTech tools in response to the Covid-19 pandemic. To support this endeavour in Pakistan, UNICEF Pakistan is building evidence on digital learning to support the EdTech ecosystem in Pakistan. Evidence in this landscape review will support stakeholders including the Ministry of Federal Education and Professional Training (MoFEPT) and UNICEF Pakistan to develop long-term strategies to fortify Pakistan’s EdTech ecosystem. The purpose of this landscape review is to identify the challenges, emerging trends, and opportunities for engagement within Pakistan’s EdTech ecosystem. To do this, the landscape analysis collected and analysed data (both primary and secondary, and quantitative and qualitative) relating to technology-facilitated learning in Pakistan. In this way, this landscape analysis can both inform MoFEPT and UNICEF’s strategies and provide a resource for stakeholder (e.g., federal, provincial, and regional government agencies, development partners, and the private sector) engagement in technology-facilitated learning in Pakistan. Keywords: marginalised learners; out-of-school children; EdTech tools; Pakistan; foundational skills; infrastructure; MoFEPT; UNICEF An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen; ⛔ No INSPIRE recid found

Using EdTech to Support Learning Remotely in the Early Years. Rapid Literature Review of Evidence from the Global Response to Covid-19. - Korin, Astrid (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org This topic brief examines the literature on technology-based, remote approaches to supporting learning in the early years for children from birth to age five, identifying promising practices for using EdTech in early childhood education (ECE) in low- and middle-income countries (LMICs). It draws on the nurturing care framework, Principles for Digital Development, and effective pedagogical practices for ECE.
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _r:AddedByZotZen; _zenodo:submitted; _zenodoETH

EdTech and Covid-19: Insights from our Sandbox Portfolio. In Collaboration with Sandbox Partner Organisations - Rahman, Asad; Plaut, Daniel; Salami, Taiye; Carter, Alice (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _r:AddedByZotZen; _zenodo:submitted

Minoritised Languages, Education, and Technology: Current practices and future directions in low- and middle-income countries - Zhao, Annette; Mitchell, Joel; Gasanabandi, Gentille; Ullah, Noor; Barnes, Katrina; Koomar, Saalim (EdTech Hub, 2024)
This article explores the current status and future directions of mother-tongue-based multilingual education (MTB MLE) and the use of technology in low- and middle-income countries (LMICs), focusing on the use of minoritised mother tongues. An initial literature review of available academic sources in multiple languages reveals a lack of evidence on the use of technology in MTB MLE across different countries, especially multilingual contexts with greater linguistic diversity. To understand the issue in greater detail and to offer recommendations informed by current practice, interviews and a collaborative workshop with four organisations with relevant educational technology (EdTech) initiatives were conducted. The analysis covers facilitating and limiting factors these organisations have encountered, and the potential positive impact on learners and society generally. We conclude by identifying practical, policy, and research priorities for multilingual education and educational technology in general.
Keywords: _r:AddedByZotZen